Characterization of the Role of Squeeze Casting on the Microstructure and Mechanical Properties of the T6 Heat Treated 2017A Aluminum Alloy - S. Souissi; N. Souissi; H. Barhoumi; M. ben Amar; C. Bradai; F. Elhalouani (Advances in Materials Science and Engineering)
In this study, the effects of squeeze casting process and T6 heat treatment on the microstructure and mechanical properties of 2017A aluminum alloy were investigated with scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDS), differential scanning calorimetry (DSC), and microhardness and tensile tests. The results showed that this alloy contained α matrix, θ-Al2Cu, and other phases. Furthermore, the applied pressure and heat treatment refines the microstructure and improve the ultimate tensile strength (UTS) to 296 MPa and the microhardness to 106 HV with the pressure 90 MPa after ageing at 180°C for 6 h. With ageing temperature increasing to 320°C for 6 h, the strength of the alloy declines slightly to 27 MPa. Then, the yield strength drops quickly when temperature reaches over 320°C. The high strength of the alloy in peak-aged condition is caused by a considerable amount of θ′ precipitates. The growth of θ′ precipitates and the generation of θ phase lead to a rapid drop of the strength when temperature is over 180°C.